2011
DOI: 10.1111/j.1365-2427.2011.02672.x
|View full text |Cite
|
Sign up to set email alerts
|

Biomass export of salamanders and anurans from ponds is affected differentially by changes in canopy cover

Abstract: 1. Previous research shows that canopy-associated shifts from an algal to a detritus-based food web can affect anuran tadpoles negatively. This may not be true of salamander larvae, however, because they are predators. 2. To investigate the influence of canopy cover on the survival and growth of salamanders, and on the subsequent export of biomass from ponds, we conducted a mesocosm experiment examining effects of shading (high or low) and litter (leaves or grass) on Ambystoma maculatum (a forest specialist) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 50 publications
4
35
1
Order By: Relevance
“…In contrast, a recent work demonstrated that the predacious larvae of two species of salamanders, grew larger in closed forest conditions (Earl et al. ). However, the authors indicate that these results are presumably due to differences in prey abundance between ponds in closed and open canopy, rather than to differences in canopy cover per se (Earl et al.…”
Section: Discussionmentioning
confidence: 91%
“…In contrast, a recent work demonstrated that the predacious larvae of two species of salamanders, grew larger in closed forest conditions (Earl et al. ). However, the authors indicate that these results are presumably due to differences in prey abundance between ponds in closed and open canopy, rather than to differences in canopy cover per se (Earl et al.…”
Section: Discussionmentioning
confidence: 91%
“…Movement of amphibians between aquatic and terrestrial habitats in the forest–wetland matrix may generate a substantial flow of nutrients and energy between breeding pools and adjacent terrestrial ecosystems (Regester & Whiles, ; Earl et al ., ; Earl & Semlitsch, ). However, the flow of energy via dispersing amphibians has been quantified only for a few species (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In wood frogs, phenotypic variation of size in post-metamorphic individuals exists at local scales and growth of larval wood frogs does differ across a latitudinal gradient (greater in northern latitudes) and temperature regimes [45], and it appears these variations can lead to differences in export biomass and standing crop of nutrients. Variations in biomass export of anurans has been shown to be influenced by canopy cover and plant litter input [31,32], but our study shows export may be influenced by phenotypic variation of post-metamorphic anuran size.…”
Section: Discussionmentioning
confidence: 54%
“…For example, a particular plant with high phenolics and high nutrient quality could reduce survival of anuran larvae, but produce larger larvae in return–thus creating a net zero or net gain in anuran biomass. Several studies have found direct relationships between higher leaf and grass detritus quality and increased anuran biomass export [30,31]. Most recently, Earl et al [32] showed high nutrient content and high secondary compounds of white oak ( Quercus alba ) resulted in measurable and distinct increases in larval anuran size, but decreases in survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation